Comprehensive analysis of particle growth rates from nucleation mode to cloud condensation nuclei in boreal forest - P. Paasonen (Atmospheric Chemistry and Physics, 2018)
Growth of aerosol particles to sizes at which they can act as cloud condensation nuclei (CCN) is a crucial factor in estimating the current and future impacts of aerosol–cloud–climate interactions. Growth rates (GRs) are typically determined for particles with diameters (dP) smaller than 40 nm immediately after a regional new particle formation (NPF) event. These growth rates are often taken as representatives for the particle growth to CCN sizes (dP > 50–100 nm). In modelling frameworks, the concentration of the condensable vapours causing the growth is typically calculated with steady state assumptions, where the condensation sink (CS) is the only loss term for the vapours. Additionally, the growth to CCN sizes is represented with the condensation of extremely low-volatility vapours and gas–particle partitioning of semi-volatile vapours. Here, we use a novel automatic method to determine growth rates from below 10 nm to hundreds of nanometres from a 20-year-long particle size distribution (PSD) data set in boreal forest. With this method, we are able to detect growth rates also at times other than immediately after a NPF event. We show that the GR increases with an increasing oxidation rate of monoterpenes, which is closely coupled with the ambient temperature. Based on our analysis, the oxidation reactions of monoterpenes with ozone, hydroxyl radical and nitrate radical all are capable of producing vapours that contribute to the particle growth in the studied size ranges. We find that GR increases with particle diameter, resulting in up to 3-fold increases in GRs for particles with dP  ∼  100 nm in comparison to those with dP  ∼  10 nm. We use a single particle model to show that this increase in GR can be explained with aerosol-phase reactions, in which semi-volatile vapours form non-volatile dimers. Finally, our analysis reveals that the GR of particles with dP < 100 nm is not limited by the condensation sink, even though the GR of larger particles is. Our findings suggest that in the boreal continental environment, the formation of CCN from NPF or sub-100 nm emissions is more effective than previously thought and that the formation of CCN is not as strongly self-limiting a process as the previous estimates have suggested.